Turtle-Based Ecotourism in the Betana Wetland of Nepal - Adhikari, Ramchandra; Basnet, Rusu; Bista, Birendra Bahadur (Bouddhik Abhiyan (बौद्धिक अभियान), 2023)
This paper attempts to analyze turtle-based ecotourism in the Betana wetland of Koshi Province, eastern Nepal. Betana is considered a nature tourism area and tourists are enjoying undeveloped natural areas of wildlife while ecotourism is a form of tourism that involved responsible travel to natural areas, conserving the environment, and improving the well-being of the local people. Nowadays, both nature tourism and ecotourism is considered the inseparable pillar of the economic development of many developing countries, like Nepal. This paper is based on primary sources of data. Data were collected from field observation, questionnaire survey, interviews, and focus group discussions. The findings reveal that Betana Wetland is located accessible area of the East-West highway in Belbari Municipality of Morang district. The ideal condition of the wetland provides a natural habitat for turtle species. A large number of tourists visit day-by-day enjoying a good habitat of turtles. The figure indicates a total of 122100 (75.23%) tourists visited the Betana wetland to watch turtles in 2017. Indeed it was 75.57 percent in 2016. The calculated F= 20.887, P value = 3.88, and F crit= 2.717 indicates that there is a close association between the patterns and the number of tourists visiting this area in different months in 2016 and 2017. The paper concludes that a visitor spent about 2.81 hours in the Betana wetland and an hour watching and playing with turtles (68.46%) for feeding, watching (9.17%), teasing (10.85%), and trying to capture (5.84%). This paper suggests that specific attention should be given to the conservation of the Betana wetland for establishing a spot of the turtle based-tourism.